Two new species of genus Lactarius (Russulaceae) from North-western Himalaya, India - Verma, Komal; Mehmood, Tahir; Uniyal, Priyanka; Kapoor, Rupam; Sharma, Yash Pal (Phytotaxa, 2021)
Two new species of genus Lactarius from India, Lactarius sarthalanus (L. subg. Plinthogalus) and L. drassinus (L. subg. Lactarius) are presented with detailed descriptions, line drawings and microphotographs. The novelty and placement of these taxa within the genus Lactarius are confirmed with ITS based phylogeny.